Low melting point glass compositions, articles and methods for making same

The novel glass compositions, characterized by specific mol% ranges of P2O5, SiO2, Al2O3, ZnO, CaO, and MgO, address the challenges of durability and carbon emissions in traditional glass production by offering a lower melting point and enhanced chemical resistance, thereby reducing CO2 emissions.

JP2025509826APending Publication Date: 2025-04-11THE PENN STATE RES FOUND INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024555338
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-15
Filing Date
2023-03-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing glass compositions face challenges in maintaining durability and chemical resistance when exposed to moisture, and they require high-temperature processing, leading to significant carbon emissions during manufacturing.

Method used

Development of novel glass compositions with a phosphorus content of about 25 to 55 mol%, silicon dioxide from 5 to 45 mol%, aluminum oxide from 5 to 22 mol%, zinc oxide from 5 to 30 mol%, and calcium or magnesium oxide from 2 to 8 mol%, which exhibit a melting point of less than 1,400°C and include up to 10 mol% iron oxide.

Benefits of technology

The new glass compositions demonstrate improved chemical durability and resistance to moisture, while reducing the carbon footprint of glass production by allowing for lower temperature processing, resulting in a significant reduction in CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509826000011
    Figure 2025509826000011
  • Figure 2025509826000012
    Figure 2025509826000012
  • Figure 2025509826000013
    Figure 2025509826000013
Patent Text Reader

Abstract

Disclosed herein are glass compositions, articles made from the disclosed glass compositions, and methods of making the same. More specifically disclosed herein are glass compositions that include about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 63 / 319,975, filed March 15, 2022, the contents of which are incorporated herein by reference in their entirety.

[0002] The present invention relates generally to novel low melting glass compositions, glass articles incorporating same, and methods of making same. [Background technology]

[0003] Millions of years ago, homo sapiens discovered the utility of naturally occurring glass. Humans learned how to make glass articles over 5,000 years ago. Modern uses of glass are very diverse and include both commercial and consumer uses. Glass is commonly used in commodity and technical applications related to the automotive industry, electronics industry, spectroscopy, and the like. Often, glass articles are also exposed to various atmospheres, and to ensure the durability of the article over time, glass compositions need to be designed to withstand such environments. For example, glass articles such as container glass, panes for windows, automobile windshields, laser host materials, fibers, tubes, and the like, used in both commodity applications such as bottles, vases, art and craft glass objects, architectural windows, automobile windshields, and technical applications such as glass tubes, glass fibers, laser host materials, often withstand the environmental attack of moisture and may lose their initial properties as a result. Thus, there is a need for glass compositions and articles containing same that can withstand exposure to moisture without losing their desired physical and chemical properties.

[0004] Glass is also known to contribute a large carbon contribution to atmospheric conditions throughout its manufacture. The use of long, high heat forming processes contributes to this carbon contribution. Glass articles generally require heat in excess of 1,450° C. for the forming process. Thus, there is a need for alternative glass compositions that can be used to produce glass articles that can be formed at lower temperatures, thereby reducing the overall carbon contribution of glass manufacture to the environment.

[0005] These needs and other needs are met, at least in part, by the present disclosure. Summary of the Invention

[0006] The present invention relates to a glass composition comprising about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total of Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.

[0007] In yet another embodiment, the glass compositions disclosed herein exhibit a melting point of less than about 1,400°C.

[0008] Additionally, the glass compositions disclosed herein may include Fe2O3 in an amount up to about 10 mol%.

[0009] Also disclosed herein are articles comprising a glass composition comprising about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.

[0010] In still further aspects, the articles disclosed herein may include food containers, tableware, cookware, glass sheets, windows, windshields, hollowware, bottles, art and craft glass objects, laser host materials, optical fibers, hollow fibers, tube fibers, laboratory usable containers, or any combination thereof.

[0011] Also disclosed herein is a method that includes a) providing about 25 to about 55 mol % P2O5, about 5 to about 45 mol % SiO2, about 5 to about 22 mol % Al2O3, about 5 to about 30 mol % ZnO, greater than 0 to about 20 mol % total Na2O, KO, and / or Li2O, about 2 to about 8 mol % CaO, and / or about 2 to about 8 mol % MgO; b) forming a homogenous mixture; and c) melting the mixture at a temperature of about 1,000° C. to about 1,300° C. and cooling the composition to form any of the glass compositions disclosed herein.

[0012] Also disclosed herein are methods of forming articles comprising forming any of the disclosed compositions. In still further aspects, the methods disclosed herein may exhibit at least about a 25% reduction in CO2 emissions compared to a reference method of making a conventional soda-lime glass composition.

[0013] Further aspects of the present disclosure are set forth in part in the following detailed description, the figures, and the claims, and in part can be derived from the detailed description or learned by the practice of the invention. It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention as disclosed. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 shows the absorption spectrum of an exemplary glass composition according to one embodiment.

[0015] [Figure 2A]2A-Elongation parameter beta evaluation. [Figure 2B] 2A-2C show the relaxation behavior of an exemplary glass composition according to one embodiment. [Figure 2C] 2C-Relaxation time evaluation of an exemplary glass composition according to one embodiment. [Figure 2D] 2A-2D-Simulated thermal history of an exemplary glass composition according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention can be more readily understood by reference to the following detailed description, examples, drawings and claims, as well as the preceding and following descriptions. However, before the present articles, systems, and / or methods are disclosed and described, it should be understood that the present invention is not limited to specific or exemplary aspects of the disclosed articles, systems, and / or methods, unless otherwise specified, and as such may, of course, vary. It should also be understood that the terminology used herein is for the purpose of describing specific aspects only, and is not intended to be limiting.

[0017] The following description of the invention is provided as an enabling teaching of the invention in its best, currently known embodiment. To this end, those skilled in the art will recognize and appreciate that many changes can be made to the various aspects of the invention described herein while still obtaining the beneficial results of the invention. It will also be apparent that some of the desired advantages of the invention can be obtained by selecting some of the features of the invention without utilizing other features. Thus, those skilled in the art will recognize that many modifications and adaptations to the invention are possible and may even be desirable in certain circumstances and are a part of the invention. Thus, the following description is again provided as an illustration of the principles of the invention, and not in limitation thereof.

[0018] definition As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to an "article" includes aspects having two or more such articles, unless the context clearly dictates otherwise.

[0019] It will be appreciated that certain features of the disclosure, which are, for clarity, described in the context of separate embodiments, can also be provided in combination in a single embodiment. Conversely, various features of the disclosure, which are, for brevity, described in the context of a single embodiment, can also be provided separately or in any suitable combination.

[0020] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances when the event or circumstance occurs and instances when it does not occur.

[0021] It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in this specification and claims, the term "comprising" can include the embodiments "consisting of" and "consisting essentially of". Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In this specification and the following claims, reference is made to a number of terms defined herein.

[0022] The terms "for example" and "such as," as well as their grammatical equivalents, are understood to be followed by the phrase "without limitation," unless otherwise noted.

[0023] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. Moreover, when numerical ranges of various scopes are set forth herein, it is contemplated that any combination of these values, including the recited values, can be used. Furthermore, ranges can be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes the one particular value and / or the other particular value.

[0024] Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it will be understood that the particular value forms another aspect. Further, the endpoints of each of the ranges will be understood to be meaningful both in relation to the other endpoint, and independently of the other endpoint. Unless otherwise stated, the term "about" means within 5% (e.g., within 2% or 1%) of the particular value modified by the term "about."

[0025] Throughout this disclosure, various aspects of the invention can be presented in a range format. It should be understood that the description in range format is merely for convenience and brevity and should not be construed as an inflexible limitation on the scope of the invention. Thus, the description of a range should be considered to have specifically disclosed all possible subranges as well as individual numerical values ​​within that range. For example, the description of a range such as 1-6 should be considered to have specifically disclosed subranges such as 1-3, 1-4, 1-5, 2-4, 2-6, 3-6, etc., as well as individual numbers within that range, such as 1, 2, 2.7, 3, 4, 5, 5.3, 6, and any whole and partial increments therebetween. This applies regardless of the breadth of the range.

[0026] As used herein, the term "composition" is intended to encompass products that contain the specified amounts of the specified components, as well as any products that result directly or indirectly from the combination of the specified amounts of the specified components. It is understood that the term "glass composition" disclosed herein refers to glass that has been melted to form a defined composition, but before it has been formed into a particular glass article. It is further understood that the glass composition as used herein is not the same as the batch components that are introduced into the mixture prior to forming the glass. In some aspects, the batch components used to form the composition may include elements that the glass composition is substantially free of.

[0027] Weight percentages (wt%) of components are based on the total weight of the formulation or composition in which the component is included, unless otherwise specified. In embodiments in which glass compositions are described, concentrations of components (e.g., SiO2, Al2O3, BO3, CuO, NiO, etc.) are given in mole percent (mol%) on an oxide basis, unless otherwise specified.

[0028] As used herein, the term "substantially" means that the subsequently described event or circumstance occurs completely, or that the subsequently described event or circumstance generally, typically, or approximately occurs.

[0029] Still further, the term "substantially" can refer in some embodiments to at least about 80%, at least about 85%, at least about 90%, at least about 91%, at least about 92%, at least about 93%, at least about 94%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, at least about 99%, or about 100% of a recited property, component, composition, or other condition used to substantially characterize or otherwise quantify an amount.

[0030] In other aspects, as used herein, the term "substantially free," when used in the context of a composition or component of a composition that is substantially free, is intended to indicate that the recited component is not intentionally batched and added to the composition, but may be present as an impurity with other components that are added to the composition. In such aspects, the term "substantially free" is intended to refer to trace amounts that may be present in a batched component, and may be present in an amount of, for example, less than about 1% by weight, e.g., less than about 0.5% by weight, less than about 0.1% by weight, less than about 0.05% by weight, or less than about 0.01% by weight of the recited material, based on the total weight of the composition.

[0031] As used herein, the term "substantially" in the context of, for example, "substantially identical" or "substantially similar" refers to a method or system, or component that is at least about 90%, at least about 91%, at least about 92%, at least about 93%, at least about 94%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, at least about 99%, or about 100% similar to the method, system, or component to which it is being compared.

[0032] It is further understood that, although the compositions disclosed herein are generally expressed as oxides, it is understood that certain elements may exist in an ionic state.

[0033] As used herein, glass transition temperature or T g The terms can be used interchangeably and are defined as the inflection point of a differential scanning calorimetry (DSC) curve during the second heat where the cooling and heating of the sample is performed at a rate of 10° C. / min and plotted as heat flow (mW) versus temperature (° C.).

[0034] As used herein, the term "melting point" refers to the temperature at which a batch material completely melts to obtain a homogeneous liquid. By glass industry convention, the melting point occurs at a liquid viscosity of approximately 10-20 Pa s.

[0035] Although aspects of the invention may be described and claimed in a particular statutory class, such as a system statutory class, this is for convenience only, and one of ordinary skill in the art will understand that each aspect of the invention may be described and claimed in any statutory class. Unless otherwise stated, it is never intended that any method or aspect described herein be interpreted as requiring that its steps be performed in a particular order. Thus, if a method claim does not specifically state in the claim or description that the steps are to be limited to a particular order, it is never intended that an order be inferred in any respect. This applies to any possible non-express basis for interpretation, including matters of logic regarding the arrangement of steps or operational flow, the plain meaning derived from grammatical construction or punctuation, or the number or type of aspects described herein.

[0036] The present invention may be understood more readily by reference to the following detailed description of the various aspects of the invention and the examples included therein, as well as the drawings and accompanying description.

[0037] The present invention may be understood more readily by reference to the following detailed description of the various aspects of the invention and the examples included therein, as well as the drawings and accompanying description.

[0038] composition In some embodiments, glass compositions are described herein that include about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.

[0039] In yet other embodiments, the glass composition may also include about 25 mol% to about 55 mol% P2O5, including exemplary values ​​of about 26 mol%, about 27 mol%, about 28 mol%, about 29 mol%, about 30 mol%, about 31 mol%, about 32 mol%, about 33 mol%, about 34 mol%, 35 mol%, about 36 mol%, about 37 mol%, about 38 mol%, about 39 mol%, about 40 mol%, about 41 mol%, about 42 mol%, about 43 mol%, about 44 mol%, about 45 mol%, about 46 mol%, about 47 mol%, about 48 mol%, and about 49 mol%.

[0040] In still further embodiments, the glass composition comprises about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 22 mol%, about 23 mol%, about 24 mol%, about 25 mol%, about 26 mol%, about 27 mol%, about 28 mol%, about 29 mol%, about 30 mol%, about 31 mol%, about 32 mol%, about 33 mol%, about 34 mol%, about 35 mol%, about 36 mol%, about 37 mol%, about 38 mol%, about 39 mol%, about 40 mol%, about 41 mol%, about 42 mol%, about 43 mol%, about 44 mol%, about 45 mol%, about 46 mol%, about 47 mol%, about 48 mol%, about 49 mol%, about 50 mol%, about 51 mol%, about 52 mol%, about 53 mol%, about 54 mol%, about 55 mol%, about 56 mol%, about 57 mol%, about 58 mol%, about 59 mol%, about 60 mol%, about 61 mol%, about 62 mol%, about 63 mol%, about 64 mol%, about 65 mol%, about 66 mol%, about 67 mol%, about 68 mol%, about 69 mol%, about 70 mol%, about 71 mol%, about 72 mol%, about 73 mol%, about 74 mol%, about 75 mol%, about 76 mol%, about 77 mol%, about In some embodiments, the SiO2 content may be about 5 to about 45 mol%, with exemplary values ​​of about 10 mol%, about 27 mol%, about 28 mol%, about 29 mol%, about 30 mol%, about 31 mol%, about 32 mol%, about 33 mol%, about 34 mol%, about 35 mol%, about 36 mol%, about 37 mol%, about 38 mol%, about 39 mol%, about 40 mol%, about 41 mol%, about 42 mol%, about 43 mol%, and about 44 mol%.

[0041] In still further embodiments, the glass composition may include from about 5 to about 22 mol% Al2O3, with exemplary values ​​of about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, and about 21 mol%.

[0042] In yet another embodiment, the glass composition can include about 5 to about 30 mol% ZnO, with exemplary values ​​of about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 22 mol%, about 23 mol%, about 24 mol%, about 25 mol%, about 26 mol%, about 27 mol%, about 28 mol%, and about 29 mol%.

[0043] Also disclosed herein are embodiments in which the glass composition comprises Na2O, K2O, and / or Li2O in a total amount of greater than 0 to about 20 mol%, including exemplary values ​​of about 0.01 mol%, about 0.05 mol%, about 1 mol%, about 2 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, and about 19 mol%. It is understood that in some embodiments, the glass composition may comprise only Na2O in any of the amounts described above. In yet other embodiments, the glass composition may comprise only Li2O in any of the amounts described above. In yet other embodiments, the glass composition may comprise only K2O in any of the amounts described above. In still further embodiments, the glass composition may include Na2O and Li2O such that the total amount of Na2O and Li2O falls within the disclosed ranges. In still further embodiments, the glass composition may include Na2O and K2O such that the total amount of Na2O and K2O falls within the disclosed ranges. In still further embodiments, the glass composition may include K2O and Li2O such that the total amount of K2O and Li2O falls within the disclosed ranges. In still further embodiments, the glass composition may include Na2O, K2O, and Li2O such that the total amount of Na2O, K2O, and Li2O falls within the disclosed ranges.

[0044] In still further embodiments, glass compositions are also disclosed in which CaO is present in an amount from about 2 mol% to about 8 mol%, including exemplary values ​​of about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, and about 7 mol%.

[0045] In still yet further embodiments, the glass compositions disclosed herein may also include about 2 to about 8 mol% MgO, including exemplary values ​​of about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, and about 7 mol%.

[0046] It is understood that in some embodiments, the glass composition can include both CaO and MgO, while in other embodiments, the glass composition can include either CaO or MgO in any of the disclosed amounts above.

[0047] In still further aspects, the glass compositions disclosed herein exhibit superior melting properties while having characteristics and properties comparable to conventional soda-lime silicate glass. It is understood that the composition of conventional soda-lime silicate glass is known. In general, with some minor deviations, soda-lime silicate glass includes about 70-75 wt.% SiO2, about 12-17 wt.% Na2O, about 7-12 wt.% CaO, greater than 0 to about 2.5 wt.% Al2O3, greater than 0 to about 1.0 wt.% K2O, greater than 0 to about 5 wt.% MgO, greater than 0 to about 0.15 wt.% Fe2O3, 0 to about 0.5 wt.% TiO2, and in some cases, 0 to about 0.5 wt.% SO3.

[0048] The melting point of soda lime silicate glass is known to be in the range of about 1,400 to about 1,450° C. In certain embodiments, the glass compositions disclosed herein exhibit melting points that are at least about 50° C., at least about 100° C., at least about 150° C., at least about 200° C., at least about 250° C., or at least about 300° C. lower than the melting points of conventional soda lime silicate glass compositions. In still further embodiments, the glass compositions disclosed herein exhibit melting points that are less than about 1,400° C., less than about 1,350° C., less than about 1,300° C., less than about 1,250° C., less than about 1,200° C., less than about 1,150° C., or less than about 1,000° C.

[0049] Without wishing to be bound by any theory, it has been observed that the thermal properties disclosed above are determined by the disclosed composition. In certain embodiments, the specific composition of the phosphates allows for the addition of Q in the network to reduce the melting temperature. 3 It is necessary to maintain a significant proportion of bonded tetrahedra while at the same time using silicate and alumina Q to enhance the chemical durability of the disclosed compositions. 4 This is determined by the need to allow for the contribution of both bonded tetrahedra. Again, without wishing to be bound by any theory, it has been observed that glass compositions having the disclosed range of phosphates allow for the achievement of the disclosed low melting points while maintaining sufficient chemical durability.

[0050] In yet another aspect, it has also been observed that the disclosed silicate range allows for sufficient chemical durability without the need for high melting temperatures. It is understood that sufficient chemical durability can be determined by the particular application. It is further understood that the actual durability can depend on the exact glass composition and the particular conditions to which it is exposed. For example, but not limited to, the conditions can include the type of solvent in which the glass is present, the pH of the solvent, the presence of corrosive elements, temperature, etc. Durability can be tailored to the particular application. For example, a glass composition used to create artistic artifacts will have a different sufficient chemical durability compared to an article used as tableware or cookware or laboratory ware. In a further aspect, the disclosed amount of alumina is sufficient to sustain the melting conditions and Q for sufficient chemical durability. 4 The bonding tetrahedra have been found to be necessary. The presence of alumina in the disclosed ranges can also impart additional mechanical stability to the glass.

[0051] In still a further aspect, it has been discovered that the disclosed amounts of ZnO can also serve to enhance the chemical durability of the glass composition without altering the electronic makeup of the glass and without substantially imparting coloration to the glass.

[0052] In still a further aspect, and without wishing to be bound by any theory, it is hypothesized that the inclusion of alkali metals and alkaline earth metals in the disclosed amounts assists in charge balance of the alumina tetrahedra, which may further reduce the melting temperature of the disclosed glass compositions.

[0053] In still further embodiments, the glass compositions disclosed herein may further comprise iron oxide. In certain embodiments, the glass compositions may comprise up to about 10 mol% Fe2O3, including exemplary amounts of about 0.01 mol%, about 0.05 mol%, about 0.1 mol%, about 0.5 mol%, about 1 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 3.5 mol%, about 4 mol%, about 4.5 mol%, about 5 mol%, about 5.5 mol%, about 6 mol%, about 6.5 mol%, about 7 mol%, about 7.5 mol%, about 8 mol%, about 8.5 mol%, about 9 mol%, and about 9.5 mol%.

[0054] In certain embodiments, up to about 0.5 mol% Fe2O3 may be present, including exemplary amounts of about 0.01 mol%, about 0.02 mol%, about 0.03 mol%, about 0.04 mol%, about 0.05 mol%, about 0.06 mol%, about 0.07 mol%, about 0.08 mol%, about 0.09 mol%, about 0.1 mol%, about 0.15 mol%, about 0.2 mol%, about 0.25 mol%, about 0.3 mol%, about 0.35 mol%, about 0.4 mol%, and about 0.45 mol%. In such exemplary, non-limiting embodiments, the glass composition may be substantially colorless.

[0055] In still further embodiments, the specific color of a glass composition can be determined spectroscopically. In some exemplary and non-limiting embodiments, when a glass composition is substantially colorless, such a composition has a color field of about 0.45 cm over the visible range of about 400 to about 800 nm, including wavelengths of about 450 nm, about 500 nm, about 550 nm, about 600 nm, about 650 nm, about 700 nm, and about 750 nm. -1 Below, approximately 0.4cm -1 Below, approximately 0.35cm -1 Below, approximately 0.3cm -1 Below, approximately 0.25cm -1 Less than or equal to 0.2 cm -1 Approximately 0.49 cm, with the following example values: -1 The following average absorption coefficients are given:

[0056] In still yet further embodiments, when the glass compositions are substantially free of color, such compositions exhibit a transmittance of greater than about 80%, greater than about 85%, greater than about 90%, greater than about 95%, or even greater than about 99% over the wavelength range of about 400 nm to about 800 nm, including about 450 nm, about 500 nm, about 550 nm, about 600 nm, about 650 nm, about 700 nm, and about 750 nm.

[0057] In yet other embodiments, such compositions can be translucent gray when Fe2O3 is present in an amount of about 0.5 to about 5 mol%, including exemplary amounts of about 0.6 mol%, about 0.6 mol%, about 0.8 mol%, about 0.9 mol%, about 1 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 3.5 mol%, about 4 mol%, and about 4.5 mol%.

[0058] In still further embodiments, the composition may also include other valences of iron oxide, such as FeO or a combination of Fe2O3 and FeO. +2 and Fe +3 It is understood that in some embodiments where both are present, the particular ratio can be determined based on the desired color. In still other embodiments, the ratio can also be influenced by the potential presence of other ions, such as, but not limited to, alkali ions or other intermediates.

[0059] In yet another embodiment, the composition may also include multiple valencies of Mn, Cr, and / or Ni to achieve the desired color of the glass.

[0060] It is understood that iron oxide is often present in the batch products used to form the disclosed glass compositions. While not wishing to be bound by any theory, it has been found that the presence of up to 0.5 mol% iron oxide in conventional soda-lime silicate glass results in edge-on green coloration, whereas the disclosed glass compositions are substantially colorless or exhibit edge-on color gray. In still further embodiments, when the amount of iron oxide is greater than about 0.5 mol%, the glass composition exhibits a translucent gray color. In still further embodiments, when the glass composition includes up to about 10 mol% iron oxide, such compositions are black in color. For example, black compositions can be defined by color coordinates, e.g., L* is 20.0 to 40.0, a* is -1.0 to 1.0, and b* is -5.0 to 2.0.

[0061] In still further aspects, the glass compositions disclosed herein may include various concentrations of additional transition metals. In certain aspects, the additional transition metals may be present as salts or oxides. In some aspects, the compositions may further include one or more transition metal oxides, including oxides of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof. It is understood that any known valence of such transition metals may be present in the compositions.

[0062] In certain embodiments, the one or more transition metal oxides are at about 0.01 mol%, about 0.05 mol%, about 0.1 mol%, about 0.15 mol%, about 0.2 mol%, about 0.25 mol%, about 0.3 mol%, about 0.35 mol%, about 0.4 mol%, about 0.45 mol%, about 0.5 mol%, about 0.55 mol%, about 0.6 mol%, about 0.65 mol%, about 0.7 mol%, about 0.75 mol%, about 0.8 mol%, about 0.85 mol%, about 0.9 mol%, about 0.95 mol%, about It is present in an amount of up to about 2 mol%, including exemplary values ​​of 1.0 mol%, about 1.05 mol%, about 1.1 mol%, about 1.15 mol%, about 1.2 mol%, about 1.25 mol%, about 1.3 mol%, about 1.35 mol%, about 1.4 mol%, about 1.45 mol%, about 1.5 mol%, about 1.55 mol%, about 1.6 mol%, about 1.65 mol%, about 1.7 mol%, about 1.75 mol%, about 1.8 mol%, about 1.85 mol%, about 1.9 mol%, and 1.95 mol%.

[0063] In still a further aspect, when one or more transition metal ions are present, such glass compositions can achieve a particular color as desired.

[0064] In yet other embodiments, the glass compositions described herein can be translucent. In still further embodiments, such exemplary and non-limiting glass compositions can exhibit a transmittance of less than about 85%, less than about 80%, less than about 75%, less than about 70%, less than about 65%, less than about 60%, less than about 55%, or less than about 50% over a wavelength range of about 400 nm to about 800 nm, including wavelengths of about 450 nm, about 500 nm, about 550 nm, about 600 nm, about 650 nm, about 700 nm, and about 750 nm.

[0065] In yet other embodiments, when copper, silver, gold, and / or tin, and / or alloys thereof are present in the composition, such metals can be reduced to generate nanoparticles within the formed glass. It is understood that in some embodiments, tin can act as a buffer to maintain the redox state of copper, silver, gold, and alloys thereof. In such exemplary embodiments, the glass composition can include a plurality of nanoparticles. Without wishing to be bound by any theory, it is envisioned that in such exemplary and non-limiting embodiments, the plurality of nanoparticles disclosed herein can provide coloration to the glass by the effect of surface plasmon resonance. In still further embodiments, these nanostructures can be developed with UV and heat treatment after formation. In still further embodiments, the glass composition can exhibit photochromic properties.

[0066] In yet further embodiments, the glass compositions disclosed herein may include one or more rare earth metal compounds. Again, without wishing to be bound by any theory, it is believed that the inclusion of rare earth metals can further provide the glass compositions disclosed herein with photoluminescent properties. Such properties in certain embodiments can be utilized to produce laser host materials as needed. In still further embodiments, the glass compositions are photoluminescent.

[0067] In certain embodiments, the one or more rare earth metal ions are present in an amount of up to about 10 mol%, including exemplary values ​​of about 0.01 mol%, about 0.05 mol%, about 0.1 mol%, about 0.5 mol%, about 1 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 3.5 mol%, about 4 mol%, about 4.5 mol%, about 5 mol%, about 5.5 mol%, about 6 mol%, about 6.5 mol%, about 7 mol%, about 7.5 mol%, about 8 mol%, about 8.5 mol%, about 9 mol%, and about 9.5 mol%.

[0068] In still further aspects, the glass compositions described herein exhibit a difference between the crystallization temperature and the glass transition temperature of greater than about 100° C. when measured at room temperature and ambient pressure. It is understood that such properties indicate resistance to crystallization and thus allow for the formation of various articles by methods known in the art, such as, for example, but not limited to, downdraw (by either slot draw or fusion draw process), fiber draw, float processing, or thin rolling of glass. In still other aspects, the method may include forming the glass into any desired shape. Various forming methods such as casting, molding, pressing, rolling, and floating may also be used. In still further aspects, the articles disclosed herein may be formed by float / flat glass press process, press and blow process, blow and blow process, or any combination thereof. In still further aspects, the method may also include glass blowing, hot casting, framework, kiln casting, and / or kiln forming. It is further understood that other low temperature glass making methods may also be utilized. For example, but not limited to, glass wheel forming methods are also contemplated.

[0069] In still further aspects, the glass compositions disclosed herein are substantially free of carbonates, however, it is understood that the batch materials used to form the glass compositions disclosed herein may contain some amounts of carbonates.

[0070] In yet a further aspect, the glass compositions disclosed herein have a glass viscosity of about 80×10 -7 K -1 Super, about 90×10 -7 K -1 Super, about 100×10 -7 K -1 Super, about 110×10 -7 K -1 Super, about 120×10 -7 K -1 Super, about 130×10 -7 K -1 Super, about 140×10 -7 K -1The linear thermal expansion coefficients are as follows:

[0071] It is understood that in some embodiments, the mechanical forming methods of the glass compositions disclosed herein need to be tailored for lower temperature operating ranges and reduced radiative heat flux losses, but with potentially significant CTEs. In some embodiments, additional cooling during the glass transition may be required. In yet other embodiments, longer annealing cycles can be used.

[0072] In still further aspects, the Vickers hardness of the glasses disclosed herein depends on the applied load. In some aspects, at a particular load (as shown in the examples below), the glass compositions disclosed herein may exhibit a Vickers hardness that is substantially equal to or less than that of a conventional soda-lime glass composition.

[0073] In still a further aspect, any of the glass compositions disclosed herein may exhibit greater crack resistance than the crack resistance of conventional soda-lime glass compositions.

[0074] Surprisingly, the glass compositions disclosed herein have been found to have significantly higher crack resistance (CR) compared to conventional soda lime. Crack resistance is defined as the force at which 50% of the corners of a Vickers indenter would be expected to have a crack, and can be thought of as the resistance of a material to crack initiation. It is a particularly important mechanical property for glass, since it can be used to characterize the damage resistance of the glass.

[0075] In still further embodiments, the glass compositions disclosed herein may exhibit a crack resistance of greater than about 0.1 kgf, greater than about 0.2 kgf, greater than about 0.3 kgf, greater than about 0.4 kgf, greater than about 0.5 kgf, greater than about 0.6 kgf, greater than about 0.7 kgf, greater than about 0.8 kgf, greater than about 0.9 kgf, or even greater than about 1.0 kgf.

[0076] Goods In certain aspects, disclosed herein are articles comprising any of the compositions disclosed above. For example, but not limited to, disclosed herein are articles comprising a glass composition comprising about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.

[0077] In still further aspects, any of the additional elements disclosed above may be present in the glass compositions used to form the articles disclosed herein.

[0078] In certain aspects, depending on the amount of iron oxide present in the compositions disclosed herein, as disclosed herein, the article may be transparent or translucent depending on the desired application. In yet further aspects, as disclosed above, the article may also be photoluminescent. It is further understood that other ions and elements may also affect the translucency of the article. For example, translucency may be achieved by any of the additives disclosed above, including, but not limited to, the addition of tin oxide.

[0079] In still further aspects, the article may include any article known in the art that requires the mechanical, chemical, and optical properties disclosed herein. In yet other aspects, the article disclosed herein may include hollowware, tableware, containers, plates, sheets (including sheets made by the float process), cookware, powders, fibers, cones, spheres, blades, or any combination thereof. In still further aspects, the article includes food containers, tableware, cookware, glass sheets, windows, windshields, hollowware, bottles, art and craft glass objects, laser host materials, optical fibers, hollow fibers, tube fibers, laboratory usable containers, or any combination thereof.

[0080] In further embodiments, articles can be formed to meet both technical requirements (such as high chemical resistance and durability, mechanical strength combined with low melting point) as well as artistic expression and aesthetic appearance. For example, but not by way of limitation, the color of the article can be controlled by varying the amount of iron oxide and / or the amount of one or more other transition oxides to form the desired article. Again, for example and without limitation, articles having darker colors can be formed. In such embodiments, articles can include colored bottles (wine bottles, beer bottles, etc.), colored pharmaceutical vials / ampoules (to protect light-sensitive pharmaceuticals), sunglasses lenses, art or craft objects, etc.

[0081] In still further aspects, the articles disclosed herein can be formed by any process. For example, the articles can be formed by float or flat press process, press and blow process, fiber draw process, blow and blow process, or any combination thereof. In still further aspects disclosed herein, the articles can also be used in various electronic devices or portable computing devices, light diffusers, automobiles, appliances, medical industry, food industry, and even architectural applications. In still further aspects, the articles disclosed herein can have any shape or configuration known in the art.

[0082] method Methods of making the disclosed compositions and disclosed articles are also disclosed herein. In certain embodiments, a method is disclosed herein that includes a) providing about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO, b) forming a homogenous mixture, and c) melting the mixture at a temperature of about 1,000°C to about 1,300°C and cooling the composition to form a glass composition.

[0083] In yet further embodiments, the glass composition is any of the glass compositions disclosed above. In still further embodiments, the mixture can be melted at a temperature between about 1,000°C and about 1,300°C, with exemplary values ​​of about 1,050°C, about 1,100°C, about 1,150°C, about 1,200°C, and about 1,250°C.

[0084] In still further aspects, any of the disclosed components and elements can be present in the mixture prior to melting.

[0085] In still yet a further aspect, a plurality of nanoparticles can be formed during the melting and cooling process and present in the cooled article.

[0086] In still further aspects, the method may further include forming any of the disclosed articles above.

[0087] In still further aspects, the glass compositions may exhibit any of the above disclosed features and characteristics. In such exemplary aspects, these compositions may be transparent, translucent, or opaque depending on the specific proportions of each component, and have any of the above disclosed color characteristics.

[0088] In still further aspects, the methods of forming the glass compositions disclosed herein exhibit at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, or at least about 50% reduction in CO2 emissions compared to a reference method of making a conventional soda-lime glass composition. It is understood that such reduction in CO2 can be explained by the low melting point of the compositions and the substantial absence of carbonates in the compositions themselves. It is also understood that such reduction in CO2 is highly desirable since glass production contributes about 86 million tons of carbon dioxide annually.

[0089] In yet another aspect, the methods disclosed herein may require at least about 30% less, at least about 35% less, at least about 40% less, at least about 45% less, or at least about 50% less btu as compared to a reference method of making a conventional soda-lime glass composition.

[0090] In still further aspects, the methods disclosed herein require at least about 50%, at least about 55%, at least about 60%, at least about 65%, or at least about 70% of the output required to make soda-lime-silicate glass.

[0091] In still further aspects, the methods disclosed herein include forming a glass article. Any method known in the art of forming or shaping an article can be utilized. For example, but not limited to, the methods of forming the glass articles disclosed herein can include downdraw (either by slot draw or fusion draw process), fiber draw, float processing, or thin rolling of glass. In still other aspects, the methods can include shaping the glass into any desired shape. Various shaping methods such as casting, molding, pressing, rolling, drawing, float, etc. can also be used. In still further aspects, the articles disclosed herein can be formed by float / flat glass press process, press and blow process, blow and blow process, or any combination thereof. In still further aspects, the methods can also include glass blowing, hot casting, framework, kiln casting, and / or kiln forming. It is further understood that other low temperature glass making methods can also be utilized. For example, but not limited to, glass wheel forming methods are also contemplated.

[0092] example The following examples are provided to provide one of ordinary skill in the art with a complete disclosure and description of how the compounds, compositions, articles, devices, and / or methods claimed herein are made and evaluated, and are intended to be purely illustrative and are not intended to limit the present disclosure. Efforts have been made to ensure accuracy with respect to numbers (e.g., amounts, temperatures, etc.), but some errors and deviations should be accounted for.

[0093] Example 1 Table 1 shows comparative properties of an exemplary article formed according to one embodiment of the present disclosure and a soda-lime-silicate article.

[0094] Example 2 Tables 2 and 3 provide exemplary, non-limiting glass compositions formed in accordance with the present disclosure.

[0095] [Table 1] [Table 2-1] [Table 2-2] [Table 3]

[0096] Table 4 shows glass compositions according to some embodiments of the present disclosure and the properties of the glass according to Ashby, MFMaterial profiles. In Materials and the Environment, 2 nd ed.; Elsevier, 2013, pp. 459-595. [Table 4]

[0097] Table 5 shows the glass transition temperatures (T) of exemplary glass compositions annealed at 700 K for 1 hour according to one embodiment of the present disclosure. g ) is shown for four uniformly distributed slow heating rates (values ​​were calculated using TransitionPy software).

[0098] FIG. 1 shows an absorption spectrum of a glass composition according to one embodiment in the wavelength range of 300 to 850 nm. [Table 5]

[0099] Table 6 shows the thermal properties of Glass 1 measured via DSC at a heating rate of 10 K.min and subsequently analyzed using Transition Py software. Values ​​are compared to soda lime silicate glasses found in Mancini, M., Sendova, M., and Mauro, JC Geometric analysis of the calorimetric glass transition and fragility using constant cooling rate cycles. JACerS [Online] 2021, 3, 348-357. https: / / ceramics.onlinelibrary.wiley.com / doi / 10.1111 / ijag.16073 and Henneberry, B. Thomas. All About Soda Lime Glass-Composition and Properties. https: / / www.thomasnet.com / articles / plant-facility-equipment / soda-lime-glass / #table. The contents of which are incorporated herein in their entirety. [Table 6]

[0100] Example 3 Figures 2A-D show the relaxation behavior of a glass composition according to one embodiment. In these exemplary plots, the glass was melted at 1.5 x Tg, quenched to room temperature at 10 °C / min, then reheated to 0.9 x Tg and held for 1 hour to relax. The elongation parameter β evolution is shown in Figure 2A. Figure 2B shows the change in viscosity, while the change in relaxation time is shown in Figure 2C. Figure 2D shows the thermal history of the simulation.

[0101] Example 4 Various glass compositions were evaluated to measure the linear coefficient of thermal expansion (CTE) and the results are shown in Table 7. [Table 7]

[0102] Example 5 The hardness of the glasses disclosed herein was further evaluated and the results are shown in Table 8.

[0103] [Table 8]

[0104] Example 6 The glass compositions disclosed herein exhibited surprisingly good crack resistance. Some of the glass compositions (shown in Table 9) had such high crack resistance that the glass did not break when a load of 1 kgf was applied. This force was found not to be high enough to produce 50% cracks. The data shows that these glasses are more than 10 times more resistant to cracking than standard soda lime. Without wishing to be bound by any theory, it was hypothesized that the overall ZnO content may play an important role in enhancing crack resistance. The measured crack resistance for the exemplary glasses is shown in Table 9.

[0105] [Table 9]

[0106] The claims are not intended to, and should not be construed as including, means-plus-function or step-plus-function limitations, unless such limitations are expressly recited in a given claim using the phrase "means for" or "step for," respectively.

[0107] In view of the processes and compositions described, certain more particularized aspects of the invention are set forth below: However, these specifically recited aspects should not be construed as having any limiting effect on any different claims that incorporate different or more general teachings set forth herein, nor should the "specific" aspects be construed as being limited in any way other than the inherent meaning of the words and formulae literally used therein.

[0108] Aspects: Aspect 1: A glass composition comprising: about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total of Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.

[0109] Aspect 2: The glass composition of aspect 1, wherein the glass composition exhibits a melting point that is at least about 150° C. lower than the melting point of a conventional soda-lime-silicate glass composition.

[0110] Aspect 3: The glass composition of Aspect 1 or 2, wherein the glass composition exhibits a melting point that is at least about 250° C. lower than the melting point of a conventional soda-lime-silicate glass composition.

[0111] Aspect 4: The glass composition of any one of aspects 1-3, wherein the glass composition exhibits a melting point of less than about 1,400° C.

[0112] Embodiment 5: The glass composition of any one of embodiments 1-4, further comprising Fe2O3 in an amount up to about 10 mol%.

[0113] Aspect 6: The glass composition of aspect 5, wherein the glass composition is substantially color-free when Fe2O3 is present at up to about 0.5 mol%.

[0114] Aspect 7: The composition has a refractive index of about 0.49 cm over the visible range of about 400 to about 800 nm. -1 7. A glass composition as recited in embodiment 6, exhibiting the following average absorption coefficients:

[0115] Aspect 8: The glass composition of aspect 6 or 7, wherein the glass composition exhibits a transmittance of greater than about 80% over a wavelength range from about 400 nm to about 800 nm.

[0116] Embodiment 9: The glass composition of embodiment 5, wherein when Fe2O3 is present in an amount between about 0.5 mol% and about 5 mol%, the glass composition is translucent gray.

[0117] Aspect 10: The glass composition of any one of aspects 1-5, further comprising one or more transition metal oxides comprising an oxide of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof.

[0118] Embodiment 11: The glass composition of embodiment 10, wherein the one or more transition metal oxides are present in an amount up to about 2 mol %.

[0119] Embodiment 12: The glass composition of embodiment 11, wherein the glass composition is translucent.

[0120] Aspect 13: The glass composition of aspect 11 or 12, wherein the glass composition exhibits a transmittance of less than about 85% over a wavelength range from about 400 nm to about 800 nm.

[0121] Aspect 14: The glass composition of any one of aspects 10-13, wherein the glass composition comprises a plurality of nanoparticles.

[0122] Embodiment 15: The glass composition of any one of embodiments 1-14, wherein the glass composition comprises one or more rare earth metal ions.

[0123] Embodiment 16: The glass composition of embodiment 15, wherein the one or more rare earth metal ions are present in an amount up to about 10 mol %.

[0124] Example 17: The glass composition of example 15 or example 16, wherein the glass composition is photoluminescent.

[0125] Aspect 18: The glass composition of any one of aspects 1 to 17, wherein the composition exhibits a difference between the crystallization temperature and the glass transition temperature of greater than about 100° C. when measured at room temperature and ambient pressure.

[0126] Aspect 19: The glass composition of any one of aspects 1-18, wherein the glass composition is substantially free of carbonate.

[0127] Aspect 20: The glass composition is about 100×10 -7 K -1 20. The glass composition according to any one of the preceding aspects, exhibiting a larger linear temperature expansion coefficient.

[0128] Embodiment 21: The glass composition of any one of embodiments 1 to 20, wherein the glass composition exhibits a crack resistance of greater than about 0.1 kgf.

[0129] Example 22: The glass composition of any one of Examples 1 to 21, wherein the glass composition exhibits a crack resistance of greater than about 0.3 kgf.

[0130] Example 23: The glass composition of any one of Examples 1 to 22, wherein the glass composition exhibits a crack resistance of greater than about 0.6 kgf.

[0131] Embodiment 24: The glass composition of any one of embodiments 1 to 23, wherein the glass composition exhibits a crack resistance of greater than about 1.0 kgf.

[0132] Example 25: An article comprising the glass composition of any one of Examples 1-24.

[0133] Example 26: The article of example 25, comprising a food container, tableware, cookware, glass sheets, windows, windshields, hollowware, bottles, art and craft glass objects, laser host materials, optical fibers, hollow fibers, laboratory usable containers, or any combination thereof.

[0134] Embodiment 27: A glass article comprising: a glass composition comprising: about 25 to about 55 mol% P2O5, about 5 to about 45 mol% SiO2, about 5 to about 22 mol% Al2O3, about 5 to about 30 mol% ZnO, greater than 0 to about 20 mol% total Na2O, K2O, and / or Li2O, about 2 to about 8 mol% CaO, and / or about 2 to about 8 mol% MgO.

[0135] Example 28: The article of example 27, wherein the glass composition exhibits a melting point at least about 150° C. lower than the melting point of a conventional soda-lime-silicate glass composition.

[0136]

[0041] Aspect 29: The article of aspect 27 or 28, wherein the glass composition exhibits a melting point that is at least about 250° C. lower than the melting point of a conventional soda-lime-silicate glass composition.

[0137] Example 30: The article of any one of examples 27-29, wherein the glass composition exhibits a melting point of less than about 1,400° C.

[0138]

[0041] Example 31: The article of any one of examples 27-30, wherein the glass composition further comprises Fe2O3 in an amount up to about 10 mol%.

[0139]

[0046] Example 32: The article of example 31, wherein the article is substantially color-free when Fe2O3 is present at up to about 0.5 mol%.

[0140] Embodiment 33: The composition has a refractive index of about 0.49 cm over the visible range of about 400 to about 800 nm. -133. The article of embodiment 32, exhibiting the following absorption coefficient averages:

[0141] Example 34: The article of example 32 or 33, wherein the article exhibits a transmittance of greater than about 80% over a wavelength range of about 400 nm to about 800 nm.

[0142] Example 35: The article of example 34, wherein when the glass composition comprises Fe2O3 present in an amount of about 0.5 mol% to about 5 mol%, the article is translucent gray.

[0143]

[0046] Example 36: The article of any one of examples 27-31, further comprising one or more transition metal oxides comprising an oxide of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof.

[0144]

[0041] Example 37: The article of example 36, wherein the one or more transition metal oxides are present in the glass composition in an amount up to about 2 mol%.

[0145]

[0046] Example 38: The article of example 37, wherein the article is translucent.

[0146] Embodiment 39: The article of any one of embodiments 37 to 38, wherein the article exhibits a transmittance of less than about 85% over a wavelength range of about 400 nm to about 800 nm.

[0147] Example 40: The article of any one of examples 36-39, wherein the glass composition comprises a plurality of nanoparticles.

[0148] Example 41: The article of any one of examples 27-40, wherein the glass composition comprises one or more rare earth metal ions.

[0149]

[0081] Example 42: The article of example 41, wherein the one or more rare earth metal ions are present in an amount up to about 10 mol%.

[0150] Example 43: The article of any one of examples 41 or 42, wherein the article exhibits photoluminescence.

[0151] Example 44: The article of any one of examples 27 to 43, wherein the glass composition exhibits a difference between the crystallization temperature and the glass transition temperature of greater than about 100° C. when measured at room temperature and ambient pressure.

[0152] Example 45: The article of any one of examples 27-44, wherein the glass composition is substantially free of carbonate.

[0153] Aspect 46: The glass composition is 100×10 -7 K -1 46. ​​The article of any one of embodiments 27-45, exhibiting a greater coefficient of linear temperature expansion.

[0154] Example 47: The article of any one of examples 27 to 46, wherein the glass composition exhibits a crack resistance of greater than about 0.1 kgf.

[0155] Example 48: The article of any one of examples 27 to 47, wherein the glass composition exhibits a crack resistance of greater than about 0.3 kgf.

[0156] Example 49: The article of any one of examples 27 to 48, wherein the glass composition exhibits a crack resistance of greater than about 0.6 kgf.

[0157] Embodiment 50: The article of any one of embodiments 27 to 49, wherein the glass composition exhibits a crack resistance of greater than about 1.0 kgf.

[0158] Embodiment 51: The article of any one of embodiments 27 to 50, comprising a food container, tableware, cookware, glass sheets, windows, windshields, hollowware, bottles, art and craft glass objects, laser host materials, optical fibers, hollow fibers, tube fibers, laboratory usable containers, or any combination thereof.

[0159] Embodiment 52: A method comprising: a) providing about 25 to about 55 mol % P2O5, about 5 to about 45 mol % SiO2, about 5 to about 22 mol % Al2O3, about 5 to about 30 mol % ZnO, greater than 0 to about 20 mol % total Na2O, KO, and / or Li2O, about 2 to about 8 mol % CaO, and / or about 2 to about 8 mol % MgO; b) forming a homogeneous mixture; and c) melting the mixture at a temperature of about 1,000° C. to about 1,300° C. and cooling the composition to form a glass composition of any one of embodiments 1 to 26.

[0160] Example 53: The method of example 52, wherein the method further comprises forming an article comprising the glass composition.

[0161] Example 54 The method of any one of examples 52 or 53, wherein the method exhibits at least about a 25% reduction in CO2 emissions as compared to a reference method of making a conventional soda-lime glass composition.

[0162] Example 55: The method of any one of examples 52-54, wherein the method comprises requiring at least about an additional btu compared to a reference method of making a conventional soda-lime glass composition.

Claims

1. 1. A glass composition comprising: About 25 to about 55 mol % P 2 O 5 , About 5 to about 45 mol % SiO 2 , About 5 to about 22 mol% Al 2 O 3 , about 5 to about 30 mol % ZnO, A total amount of Na of more than 0 to about 20 mol% 2 O.K. 2 O and / or Li 2 O. about 2 to about 8 mol % CaO, and / or About 2 to about 8 mol % MgO A glass composition comprising:

2. 10. The glass composition of claim 1, wherein the glass composition exhibits a melting point at least about 150°C lower than the melting point of conventional soda-lime-silicate glass compositions.

3. 3. The glass composition of claim 1, wherein the glass composition exhibits a melting point that is at least about 250° C. lower than the melting point of conventional soda-lime-silicate glass compositions.

4. The glass composition according to any one of claims 1 to 3, wherein the glass composition exhibits a melting point of less than about 1,400°C.

5. Fe in an amount of up to about 10 mol% 2 O 3 The glass composition according to any one of claims 1 to 4, further comprising:

6. Fe 2 O 3 The glass composition of claim 5 , wherein the glass composition is substantially color-free when present at up to about 0.5 mol %.

7. The composition has an average viscosity of about 0.49 cm over the visible range of about 400 to about 800 nm. -1 7. The glass composition of claim 6, which exhibits an average absorption coefficient of:

8. 8. The glass composition of claim 6, wherein the glass composition exhibits a transmittance of greater than about 80% over a wavelength range from about 400 nm to about 800 nm.

9. Fe 2 O 3 The glass composition of claim 5 , wherein when is present in an amount from about 0.5 mol % to about 5 mol %, the glass composition is translucent gray in color.

10. The glass composition of any one of claims 1 to 5, further comprising one or more transition metal oxides comprising an oxide of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof.

11. 11. The glass composition of claim 10, wherein the one or more transition metal oxides are present in an amount up to about 2 mol%.

12. 12. The glass composition of claim 11, wherein the glass composition is translucent.

13. 13. The glass composition of claim 11 or 12, wherein the glass composition exhibits a transmission of less than about 85% over a wavelength range from about 400 nm to about 800 nm.

14. The glass composition according to any one of claims 10 to 13, wherein the glass composition comprises a plurality of nanoparticles.

15. The glass composition according to any one of claims 1 to 14, wherein the glass composition comprises one or more rare earth metal ions.

16. 16. The glass composition of claim 15, wherein the one or more rare earth metal ions are present in an amount up to about 10 mol %.

17. 17. The glass composition of claim 15 or 16, wherein the glass composition is photoluminescent.

18. 18. A glass composition according to any one of claims 1 to 17, exhibiting a difference between the crystallization temperature and the glass transition temperature of more than about 100°C when measured at room temperature and ambient pressure.

19. The glass composition according to any one of claims 1 to 18, wherein the glass composition is substantially free of carbonate.

20. The glass composition is 100×10 -7 K -1 A glass composition according to any one of the preceding claims, exhibiting a larger linear temperature expansion coefficient.

21. The glass composition according to any one of claims 1 to 20, wherein the glass composition exhibits a crack resistance of greater than about 0.1 kgf.

22. The glass composition according to any one of claims 1 to 21, wherein the glass composition exhibits a crack resistance of greater than about 0.3 kgf.

23. The glass composition according to any one of claims 1 to 22, wherein the glass composition exhibits a crack resistance of greater than about 0.6 kgf.

24. The glass composition according to any one of claims 1 to 23, wherein the glass composition exhibits a crack resistance of greater than about 1.0 kgf.

25. An article comprising the glass composition according to any one of claims 1 to 24.

26. 26. The article of claim 25, comprising a food container, tableware, cookware, glass sheets, windows, windshields, hollowware, bottles, arts and crafts glass objects, laser host materials, optical fibers, hollow fibers, laboratory usable containers, or any combination thereof.

27. About 25 to about 55 mol % P 2 O 5 , About 5 to about 45 mol % SiO 2 , About 5 to about 22 mol% Al 2 O 3 , about 5 to about 30 mol % ZnO, A total amount of Na of more than 0 to about 20 mol% 2 O.K. 2 O and / or Li 2 O. about 2 to about 8 mol % CaO, and / or About 2 to about 8 mol % MgO A glass composition comprising: Glass articles, including

28. 30. The article of claim 27, wherein the glass composition exhibits a melting point at least about 150°C lower than the melting point of conventional soda-lime-silicate glass compositions.

29. 30. The article of claim 27 or 28, wherein the glass composition exhibits a melting point at least about 250° C. lower than the melting point of conventional soda-lime-silicate glass compositions.

30. The article of any one of claims 27 to 29, wherein the glass composition exhibits a melting point of less than about 1,400°C.

31. The glass composition comprises Fe 2 O 3 The article of any one of claims 27 to 30, further comprising:

32. Fe 2 O 3 32. The article of claim 31, wherein the article is substantially free of color when is present at up to about 0.5 mol%.

33. The composition has an average viscosity of about 0.49 cm over the visible range of about 400 to about 800 nm. -1 33. The article of claim 32, exhibiting an absorption coefficient average of:

34. 34. The article of claim 32 or 33, wherein the article exhibits a transmittance of greater than about 80% over the wavelength range of about 400 nm to about 800 nm.

35. The glass composition comprises Fe, present in an amount of about 0.5 mol % to about 5 mol %. 2 O 3 35. The article of claim 34, wherein when the article comprises

36. The article of any one of claims 27-31, further comprising one or more transition metal oxides comprising an oxide of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof.

37. 37. The article of claim 36, wherein the one or more transition metal oxides are present in the glass composition in an amount up to about 2 mol%.

38. 40. The article of claim 37, wherein the article is translucent.

39. 39. The article of claim 37 or 38, wherein the article exhibits a transmittance of less than about 85% over the wavelength range of about 400 nm to about 800 nm.

40. The article of any one of claims 36 to 39, wherein the glass composition comprises a plurality of nanoparticles.

41. The article of any one of claims 27 to 40, wherein the glass composition comprises one or more rare earth metal ions.

42. 42. The article of claim 41, wherein the one or more rare earth metal ions are present in an amount up to about 10 mol%.

43. 43. The article of claim 41 or 42, wherein the article exhibits photoluminescence.

44. 44. The article of any one of claims 27 to 43, wherein the glass composition exhibits a difference between crystallization temperature and glass transition temperature of more than about 100°C when measured at room temperature and ambient pressure.

45. The article of any one of claims 27 to 44, wherein the glass composition is substantially free of carbonates.

46. The glass composition is 100×10 -7 K -1 The article of any one of claims 27 to 45, exhibiting a greater coefficient of linear temperature expansion.

47. The article of any one of claims 27 to 46, wherein the glass composition exhibits a crack resistance of greater than about 0.1 kgf.

48. The article of any one of claims 27 to 47, wherein the glass composition exhibits a crack resistance of greater than about 0.3 kgf.

49. The article of any one of claims 27 to 48, wherein the glass composition exhibits a crack resistance of greater than about 0.6 kgf.

50. The article of any one of claims 27 to 49, wherein the glass composition exhibits a crack resistance of greater than about 1.0 kgf.

51. 51. The article of any one of claims 27-50, comprising a food container, tableware, cookware, glass sheets, windows, windshields, hollowware, bottles, art and craft glass objects, laser host materials, optical fibers, hollow fibers, tube fibers, laboratory usable containers, or any combination thereof.

52. a) About 25 to about 55 mol % P 2 O 5 , About 5 to about 45 mol % SiO 2 , About 5 to about 22 mol% Al 2 O 3 , about 5 to about 30 mol % ZnO, A total amount of Na of more than 0 to about 20 mol% 2 O.K. 2 O and / or Li 2 O. about 2 to about 8 mol % CaO, and / or About 2 to about 8 mol % MgO and b) forming a homogenous mixture; and c) melting the mixture at a temperature of about 1,000° C. to about 1,300° C.; d) cooling the composition to form a glass composition according to any one of claims 1 to 26; and A method comprising:

53. 53. The method of claim 52, wherein the method further comprises forming an article comprising the glass composition.

54. The method is characterized in that it reduces CO 2 54. The method of claim 52 or 53, which exhibits at least about a 25% reduction in excretion.

55. 55. The method of any one of claims 52-54, wherein the method requires at least about 30% less btu as compared to a reference method of making a conventional soda-lime glass composition.